A Deep Learning System for Automated Angle-Closure Detection in Anterior Segment Optical Coherence Tomography Images - Fu, Huazhu; Baskaran, Mani; Xu, Yanwu; Lin, Steve; Wong, Damon Wing Kee; Liu, Jiang; Tun, Tin A.; Mahesh, Meenakshi; Perera, Shamira A.; Aung, Tin (American Journal of Ophthalmology, 2019)
Purpose Anterior segment optical coherence tomography (AS-OCT) provides an objective imaging modality for visually identifying anterior segment structures. An automated detection system could assist ophthalmologists in interpreting AS-OCT images for the presence of angle closure. Design Development of an artificial intelligence automated detection system for the presence of angle closure. Methods A deep learning system for automated angle-closure detection in AS-OCT images was developed, and this was compared with another automated angle-closure detection system based on quantitative features. A total of 4135 Visante AS-OCT images from 2113 subjects (8270 anterior chamber angle images with 7375 open-angle and 895 angle-closure) were examined. The deep learning angle-closure detection system for a 2-class classification problem was tested by 5-fold cross-validation. The deep learning system and the automated angle-closure detection system based on quantitative features were evaluated against clinicians' grading of AS-OCT images as the reference standard. Results The area under the receiver operating characteristic curve of the system using quantitative features was 0.90 (95% confidence interval [CI] 0.891–0.914) with a sensitivity of 0.79 ± 0.037 and a specificity of 0.87 ± 0.009, while the area under the receiver operating characteristic curve of the deep learning system was 0.96 (95% CI 0.953–0.968) with a sensitivity of 0.90 ± 0.02 and a specificity of 0.92 ± 0.008, against clinicians' grading of AS-OCT images as the reference standard. Conclusions The results demonstrate the potential of the deep learning system for angle-closure detection in AS-OCT images.